A Review of The Factors That Form The Brand Equity Of Public Hospitals: A Quantitative Study In Tangerang City - Hasanah, Nur; Syah, Tantri Yanuar Rahmat; Rojuaniah, Rojuaniah; Astuti, Puji; Suyitno, Edy (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
An important tactic for businesses in establishing and sustaining their place in the market is the expansion of their brand's equity through various marketing channels. The purpose of this research is to identify the factors that affect RSU Bhakti Asih Tangerang's brand equity and loyalty through social media marketing, brand association, brand image, and brand awareness. The researchers at RSU Bhakti Asih Tangerang used a selective selection technique to choose 145 general patients who were not BPJS. The Structural Equation Model was used for data analysis. According to this research, there is a favorable correlation between brand equity, brand loyalty, social media marketing, and brand image; nevertheless, brand equity is unaffected by brand awareness and association. This study's managerial implications include the following: RSU Bhakti Asih should work on raising brand recognition and positive associations with the brand in order to boost Brand Equity; if the company succeeds in doing so, its customers will never buy from its rivals